Moving forward or standing still? A reflection of 'special' educational provision in Malaysia. Issue 4 (3rd July 2016) - Chong, Pei Wen
ABSTRACT: This paper investigates influential discourses embedded within policy documents and policy-makers' accounts to trace special education development in Malaysia. With a heavy reliance on the medical model, the distinction of the 'educable' and 'ineducable' based on self-care abilities is incongruent with inclusive ideals that support learner diversity. The diagnosed disability types of students bear a strong influence on their educational settings and learning pathways, leading to many students with physical impairments relegated to community care centres outside the schooling system. The proportion of pupils in special schools remains low, yet special classes are expanding exponentially resulting from growing diagnoses of various kinds of learning disabilities, particularly the category of 'slow learner'. This calls into question whether the increasing use of special classes leads to an improvement of support provision or the growing failings of the Malaysian general education system.